Implementasi Perlindungan Hukum Upah Pekerja/Buruh Kontrak Oleh Dinas Ketenagakerjaan, Perindustrian Dan Perdagangan Di Kabupaten Batu Bara - Manurung, Mangaraja; Rohela, Rohela (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
Legal protection aims to guarantee workers' rights, particularly for contract workers, regarding fair wages that should be ensured by law, including the latest regulations governing the mechanisms and procedures for employment relationships with contract workers, namely Law No. 6 of 2023 and Government Regulation No. 35 of 2021. The issue at hand is that many companies continue to neglect the rights of contract workers, with instances of discrimination occurring in various industrial sectors. Based on the research conducted, this study employs an empirical legal method by collecting primary and secondary data to analyze legal protection for contract workers in Batu Bara Regency. The findings indicate that the Batu Bara Regency Manpower Office has made maximum efforts to provide legal protection and uphold the rights of contract workers through non-litigation mechanisms. Data shows an increase in the minimum wage in North Sumatra, from IDR 2,809,915 (2024) to IDR 2,992,559 (2025), and in Batu Bara Regency from IDR 3,451,671 to IDR 3,676,000. Among 17 companies in Batu Bara Regency, there are 2,031 contract workers, with 63 cases of labor rights disputes and employment termination between 2019 and 2023 that have been resolved through mediation or negotiation. The challenges in the field indicate that, in practice, the protection of wage rights for contract workers in Batu Bara Regency has been implemented by the Manpower Office in accordance with national, provincial, and regency-level policies to ensure a decent livelihood for contract workers through supervision, preventive, and repressive measures. However, the neglect of workers' rights by certain companies remains a critical issue in guaranteeing contract workers' legal protection.